Sport Climbing as an Extracurricular Activity in Primary School - Anja Unuk; Blaž Jereb (CV. AULIANTECH, 2026)
Sport climbing is experiencing a rapid surge in popularity within the Slovenian educational landscape, largely driven by international competitive success and a growing recognition of its multifaceted benefits for childhood motor development, including significant improvements in coordination, flexibility, endurance, and upper-body strength. Despite the widespread installation of climbing infrastructure in school gymnasiums across the country, a critical research gap persists regarding the effective utilization of these facilities, as recent data indicates that over fifty percent of physical education teachers report a lack of professional competence and technical confidence in delivering climbing-specific content. To address this institutional challenge, the present study employs a descriptive methodological framework and a synthesis of expert pedagogical experience to develop a comprehensive instructional system specifically tailored for the primary school environment. The research centers on the critical paradigm of equipment literacy as a foundational safety prerequisite, moving beyond mere technical operation to foster a deep-seated culture of responsibility and risk management among young learners. The primary output of this study is a structured, evidence-based curriculum featuring nine progressive lesson plans designed to span three distinct three-year developmental periods, ensuring that skill acquisition is age-appropriate and methodologically sound. By prioritizing the safety chain and the implementation of top-rope climbing utilizing modern self-locking belay devices, the study provides a scientifically grounded and ready-to-use resource that bridges the prevailing gap between available school infrastructure and teacher instructional capacity. This framework ultimately enhances the quality of extracurricular sports programs, promotes institutional safety standards, and fosters a sustainable culture of lifelong physical literacy and athletic engagement among primary school students.